Strategi Digital Micro Financing dan Manajemen Arus Kas Untuk Mendorong Inklusi Keuangan UMKM - Made Irma Lestari; Wijanarko, Hubertus Maria Rosariandoko; Rahim, Norizan Baba; Marsintauli, Frihardina; Simon (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in Indonesia’s economy, yet they face challenges in accessing financing and managing cash flow. This study aims to explore strategies for leveraging digital technology in micro financing and cash flow management, as well as their impact on enhancing financial inclusion for MSMEs in Indonesia. Innovative approaches such as Peer-to-Peer (P2P) lending and mobile-based cash flow management applications can expand the reach of financial services and improve business efficiency. The study analyzes the outcomes of an international hybrid seminar entitled “Micro Financing in Action: Strategies for Financial Inclusion” organized by Accounting Binus Online and Universiti Sains Malaysia (USM). Participants—including MSME practitioners, students, and the general public—received training on the importance of micro financing, the role of P2P lending, and the use of digital financial management applications. The results of pre- and post-test analysis using a paired sample t-test revealed a significant increase in participants’ knowledge after the training. These findings demonstrate that combining training on digital financing and technology-based cash management can effectively enhance participants’ financial literacy and is expected to improve financial inclusion for MSMEs.